Blocking type TSH receptor antibodies - Furmaniak, Jadwiga; Sanders, Jane; Rees Smith, Bernard (Autoimmunity highlights, 2013)
TSH receptor (TSHR) autoantibodies (TRAbs) play a key role in the pathogenesis of Graves’ disease. In the majority of patients, TRAbs stimulate thyroid hormone synthesis via activation of the TSHR (stimulating TRAbs, TSHR agonists). In some patients, TRAbs bind to the receptor but do not cause activation (blocking TRAbs, TSHR antagonists). Isolation of human TSHR monoclonal antibodies (MAbs) with either stimulating (M22 and K1-18) or blocking activities (5C9 and K1-70) has been a major advance in studies on the TSHR. The binding characteristics of the blocking MAbs, their interaction with the TSHR and their effect on TSHR constitutive activity are summarised in this review. In addition, the binding arrangement in the crystal structures of the TSHR in complex with the blocking MAb K1-70 and with the stimulating MAb M22 (2.55 Å and 1.9 Å resolution, respectively) are compared. The stimulating effect of M22 and the inhibiting effect of K1-70 on thyroid hormone secretion in vivo is discussed. Furthermore the ability of K1-70 to inhibit the thyroid stimulating activity of M22 in vivo is shown . Human MAbs which act as TSHR antagonists are potentially important new therapeutics. For example, in Graves’ disease, K1-70 may well be effective in controlling hyperthyroidism and the eye signs caused by stimulating TRAb. In addition, hyperthyroidism caused by autonomous TSH secretion should be treatable by K1-70, and 5C9 has the potential to control hyperthyroidism associated with TSHR activating mutations. Furthermore, K1-70 has potential applications in thyroid imaging as well as targeted drug delivery to TSHR expressing tissues.